DEVELOPMENT OF ENVIRONMENTAL EDUCATION AND TOLERANCE AMONG YOUNG PEOPLE IS AN IMPORTANT FACTOR OF SOCIETY’S DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article details and highlights the negative impact of the environmental crisis, which is one of the global problems of the modern world on the life of society, the role and place of environmental education in the formation of youth, the legal foundations of environmental education, the development of pedagogical forms and methods of teaching it. The article also pays attention to such issues as ways and directions to increase environmental tolerance in society, the development of the phenomenon of tolerance in social and environmental activities, and the reflection in the state strategy for the development of environmental education problems.